2017
DOI: 10.3390/nano8010016
|View full text |Cite
|
Sign up to set email alerts
|

PEG 400-Based Phase Change Materials Nano-Enhanced with Functionalized Graphene Nanoplatelets

Abstract: This study presents new Nano-enhanced Phase Change Materials, NePCMs, formulated as dispersions of functionalized graphene nanoplatelets in a poly(ethylene glycol) with a mass-average molecular mass of 400 g·mol−1 for possible use in Thermal Energy Storage. Morphology, functionalization, purity, molecular mass and thermal stability of the graphene nanomaterial and/or the poly(ethylene glycol) were characterized. Design parameters of NePCMs were defined on the basis of a temporal stability study of nanoplatelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
45
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 68 publications
(104 reference statements)
13
45
2
1
Order By: Relevance
“…This trend is in agreement with that predicted from C p data measured in our laboratory for the base fluid and dry PVP-capped Ag nanoparticles by using Equation (1). Other studies on nanofluids using PEG400 as base fluid found diminutions of 3% for the concentration of 1wt% of multiwalled carbon nanotubes (MWCNT) [32], or 0.34% for a dispersion of 0.5 wt% using functionalized graphene nanoplatelets [30]. Hence, it can be concluded that the addition of the PVP-capped Ag nanoparticles does not lead to a significant reduction in the sensible heat capacity of the phase change material.…”
Section: Isobaric Heat Capacitysupporting
confidence: 89%
See 4 more Smart Citations
“…This trend is in agreement with that predicted from C p data measured in our laboratory for the base fluid and dry PVP-capped Ag nanoparticles by using Equation (1). Other studies on nanofluids using PEG400 as base fluid found diminutions of 3% for the concentration of 1wt% of multiwalled carbon nanotubes (MWCNT) [32], or 0.34% for a dispersion of 0.5 wt% using functionalized graphene nanoplatelets [30]. Hence, it can be concluded that the addition of the PVP-capped Ag nanoparticles does not lead to a significant reduction in the sensible heat capacity of the phase change material.…”
Section: Isobaric Heat Capacitysupporting
confidence: 89%
“…Experimental isobaric heat capacities, Cp, for PEG400, the dry powder of Ag nanoparticle, and the Ag(0.5 wt%)/PEG400 nanofluid in the temperature range from 283.15 to 333.15 K are shown in Figure 7. Obtained values for base fluid exhibit a good agreement with data reported by Francesconi et al [70] and Marcos et al [30,32] for other poly(ethylene glycol) with similar average molecular weights, around 400 g•mol −1 . Results measured for dry silver nanoparticles were also compared with the values recommended by Touloukian and Buyco [71] for bulk silver.…”
Section: Isobaric Heat Capacitysupporting
confidence: 89%
See 3 more Smart Citations